Sistem Pendukung Keputusan Untuk Memilih BTS (Base Transceiver Station) Service Terburuk dengan Menerapkan Fuzzy MADM - Sianturi, Hotman Jandri Vay; Sianturi, Lince Tomoria (Forum Kerjasama Pendidikan Tinggi, 2021)
Information about the performance of a BTS (Base Transceiver Station) is needed to help improve a Network service. But in the selection of a good or bad BTS (Base Transceiver Station) it can be caused by several factors such as Transmission, Power, and Celldown BTS. Therefore we need a system that can provide recommendations using the right method, here are the decision support system methods including Fuzzy Multiple Attribute Decision Making TOPSIS. The TOPSIS method uses the principle that the chosen alternative must have the closest distance from the positive ideal solution and the longest (farthest) distance from the negative ideal solution from a geometric point of view using Euclidean distance (distance between two points) to determine the relative proximity of an alternative with the optimal solution . Positive ideal solutions are defined as the sum of all the best values ​​that can be achieved for each attribute, while the negative-ideal solution consists of all the worst values ​​achieved for each attribute. while the negative-ideal solution consists of all the worst values ​​achieved for each attribute.